IMPACT OF DIABETES ON LABORATORY MARKERS IN NON-ST ELEVATED ACUTE CORONARY SYNDROME PATIENTS- A CROSS-SECTIONAL STUDY. - Jyoti Prakash Lal Karn; Naween Kumar; Prakash Ranjan (Student's Journal of Health Research, 2023)
Background: The diabetic population is known to be at a significantly increased risk of developing cardiovascular complications, particularly in the context of acute coronary syndromes. The present study sought to examine the impact of diabetes on the primary biochemical and hematological indicators in individuals diagnosed with non-ST elevation acute coronary syndromes (NSTE-ACS). Methods: A multicenter cross-sectional study collected data from NSTEACS patients who were admitted and diagnosed using a printed form to record age, comorbidities, and investigation Results. The patients were divided into diabetics and non-diabetics. Results: Ninety-nine patients were enrolled, 39.4% were diabetic, the mean age of diabetics was (60.7 ± 11.0) years vs. (58.3 ± 13.4) years in non-diabetics; diabetic patients were more to be female 22.9% vs 22.3%, more to have IHD history 59.13% vs 34.8%, more be hypertensive 68.8% vs 54.08%, less to be smokers 32.7% vs 37.7% and hyperlipidaemic 29.2% vs 32.7% when compared to non-diabetic counterparts, however, the differences in baseline characteristics between the two groups did not reach statistical significance apart from the more reported history of IHD in diabetics; p=0.019. Conclusion: In the context of non-ST segment elevation acute coronary syndrome (NSTE-ACS), it is noteworthy that diabetes mellitus does not exhibit any significant influence on biochemical and hematological markers, except for elevated blood glucose and serum potassium levels, when compared to individuals without diabetes. Recommendation: Further investigations are warranted to substantiate these findings and evaluate the prognostic implications of laboratory indicators in individuals with diabetes experiencing acute coronary syndromes, particularly in resource-limited regions where the utilization of more advanced markers may not be feasible.